Association of improved outcome in acute ischaemic stroke patients with atrial fibrillation who receive early antithrombotic therapy: analysis from VISTA. (16th October 2014) - Abdul‐Rahim, A. H.; Fulton, R. L.; Frank, B.; Tatlisumak, T.; Paciaroni, M.; Caso, V.; Diener, H.‐C.; Lees, K. R.; the VISTA collaborators
<x xml:space="preserve">Abstract</x> Background and purpose Ischaemic stroke patients with atrial fibrillation (AF) are at risk of early recurrent stroke (RS). However, antithrombotics commenced at the acute stage may exacerbate haemorrhagic transformation, provoking symptomatic intracerebral haemorrhage (SICH). The relevance of antithrombotics on the patterns and outcome of the cohort was investigated. Methods A non‐randomized cohort analysis was conducted using data obtained from VISTA (Virtual International Stroke Trials Archive). The associations of antithrombotics with the modified Rankin Scale (mRS) outcome and the occurrence of RS and SICH (each as a combined end‐point of fatal and non‐fatal events) at 90 days for post‐stroke patients with AF were described. Dichotomized outcomes were also considered as a secondary end‐point (i.e. mortality and good outcome measure at 90 days). Results In all, 1644 patients were identified; 1462 (89%) received antithrombotics, 157 (10%) had RS and 50 (3%) sustained SICH by day 90. Combined antithrombotic therapy (i.e. anticoagulants and antiplatelets), 782 (48%), was associated with favourable outcome on ordinal mRS and a significantly lower risk of RS, SICH and mortality by day 90, compared with the no antithrombotics group. The relative risk of RS and SICH appeared highest in the first 2 days post‐stroke before attenuating to become constant over time. Conclusions The risks and benefits of antithrombotics in recent stroke patients with AF appear to track together. Early introduction of anticoagulants (2–3 days post‐stroke), and to a lesser extent antiplatelet agents, was associated with substantially fewer RS events over the following weeks but with no excess risk of SICH. More evidence is required to guide clinicians on this issue.